2019
DOI: 10.4274/haseki.galenos.2019.4794
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Rates in Geriatric Outpatient Clinic in Gaziantep Dr. Ersin Arslan Training and Research Hospital

Abstract: Aim: Vaccination against influenza, pneumococcal disease, herpes zoster and tetanus-diphtheria-acellular pertussis (Tdap) is recommended for older adults. Data on vaccination rates in older adults are limited for our country. We aimed to investigate the prevalence of vaccination in community-dwelling older adults. Methods: Patients >= 65 years admitted to Dr. Ersin Arslan Research and Training Hospital geriatric outpatient clinic between September 2017 and May 2018 in Gaziantep were included. Demographic data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2019
2019
2026
2026

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…In the study of Bolatkale et al 27 it was determined that 59% of the participants had a tetanus vaccine and 53.2% of them had it in the last 5 years, and the first reason for vaccination was sharp object injuries with 50.6%. Yürüyen et al 14 found the tetanus vaccination rate to be much lower (5%) than our study result, while İlhan and Bakkaloğlu 16 reported that no patients were vaccinated for tetanus and HZ. It is stated that 82% of adults have received the tetanus vaccine in the last 10 years, 65% of those aged 65 and over have received the seasonal influenza vaccine, and 42% have received the pneumococcal vaccine in Canada, which is higher than our study results.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In the study of Bolatkale et al 27 it was determined that 59% of the participants had a tetanus vaccine and 53.2% of them had it in the last 5 years, and the first reason for vaccination was sharp object injuries with 50.6%. Yürüyen et al 14 found the tetanus vaccination rate to be much lower (5%) than our study result, while İlhan and Bakkaloğlu 16 reported that no patients were vaccinated for tetanus and HZ. It is stated that 82% of adults have received the tetanus vaccine in the last 10 years, 65% of those aged 65 and over have received the seasonal influenza vaccine, and 42% have received the pneumococcal vaccine in Canada, which is higher than our study results.…”
Section: Discussioncontrasting
confidence: 74%
“…28 Because HZ and pneumococci vaccines are not covered by social security institutions in Turkey, vaccination rates are reported to be low. 16 In our study, tetanus vaccination of patients who were married and who resided in the province was significantly higher. The reason for this was that the study was conducted in the city, and spousal support might have facilitated access to health services.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Three studies reported the proportion of individuals vaccinated for HZ in Turkey. Notably, all three studies reported markedly low HZ immunization rates, compared with pneumococcus and influenza (Table 3 ) [ 99 , 100 , 104 ]. For example, a study of 488 individuals ≥ 65 years of age diagnosed with a chronic disease reported that only 0.8% were vaccinated for HZ compared with 2.7% and 32.8% for pneumococcus and influenza, respectively [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…Findings from Bangladesh and Turkey suggest that immunization of households with children with CP may be overlooked in low-to middle-income countries. In 2019, influenza and pneumococcal immunization rates among ≥ 65-year-old healthy subjects in Turkey were 8.2% and 0.2%, respectively; immunization rates among Turkish adults with the chronic obstructive pulmonary disease were 37.9% and 13.3%, respectively (19,20). These rates suggest that treating parents/grandparents necessitate developing awareness of the risk for transmission of vaccinepreventable diseases among households and preventive strategies to protect both themselves and their children/ grandchildren.…”
Section: Discussionmentioning
confidence: 99%